Adverse Events Related to Acupuncture. Issue 10 (October 2015) - Chung, Ka-Fai; Yeung, Wing-Fai; Yu, Yee-Man; Kwok, Chi-Wa; Zhang, Shi-Ping; Zhang, Zhang-Jin
<x xml:space="preserve">Abstract</x> Objectives: Mild adverse events (AEs) are common with acupuncture, but the collection of AEs is generally poor. The objective of this study was to develop and test a new instrument for acupuncture-related AEs. Materials and Methods: After literature review, consultation with experts, and pilot-testing, the acupuncture-related AE report form (AcupAE), a 20-item scale on local and systemic AEs was tested in 150 adults who were randomized to receive acupuncture, minimal acupuncture, and placebo acupuncture. AE was assessed using open-ended questioning, followed by the AcupAE after the third, sixth, and ninth treatment. Results: The incidence of any AEs per patient, as derived from the AcupAE, was 42.4% with acupuncture, 42.2% with minimal acupuncture, and 16.7% with placebo acupuncture; the respective incidence was 6.8%, 5.1%, and 3.3% with open-ended questioning. There was a significant difference in the incidence of any AEs between the 3 groups based on the AcupAE, and the incidence rates of any AEs were significantly higher when assessed by the AcupAE than by open-ended questioning in the acupuncture and minimal acupuncture groups. Discussion: The AcupAE was able to detect differences in AE between true, minimal, and simulated acupuncture, whereas the open-ended questioning was not sensitive enough. The results support the use of AcupAE as an effective instrument for the assessment of acupuncture-related AEs. Although the checklist approach can result in overreporting and the causality may be unclear for some events, it is the first step for collecting standardized information and allowing comparison between different acupuncture approaches and patient groups in future studies.